Role of phosphorylation at Toc159 in chloroplast protein import and identification of a new outer chloroplast membrane kinase - (:unkn) unknown (My University, 2025)
Chloroplast are essential organelles in plants and the home of photosynthesis. They are responsible for biomass and food production on the planet. Chloroplasts develop in plant leaves when they are exposed to light. This process is also known as chloroplast biogenesis. During chloroplast biogenesis, hundreds of different proteins are imported to build the photosynthetic apparatus. The import of proteins into the chloroplasts requires a protein import machinery that consists of the TOC and TIC complexes (translocons at the outer and inner membrane of chloroplasts, respectively). In this project, we are interested in a protein import receptor called Toc159 (159 stands for the mass in kilodaltons). Plants that are mutated in Toc159 have neither chloroplasts nor chlorophyll and are albino. Toc159 consists of three parts, one of which (the acidic A-domain) at the start of the protein is needed for regulation. We know that the A-domain becomes hyper-phosphorylated by several different kinases. One such kinase, KOC1, is a focus of this project. The A-domain can also be removed by proteases. But we do not yet know the exact purpose of the phosphorylation or the removal by proteases. In this project, we will make artificial versions of Toc159 that cannot be phosphorylated or cut at the A-domain. These highly sophisticated synthetic versions of Toc159 will help us understand the phosphorylation at the A-domain and why it sometimes can be removed by proteases. Overall, this project will deepen our insight into the regulatory mechanisms at the key import receptor Toc159. In the future, we expect application of this knowledge in breeding projects that could lead to plants that photosynthesize more effectively and yield more biomass and food in agriculture.
Keywords: Chloroplasts; Arabidopsis thaliana; Phosphorylation; Processing; Protein import